2013
DOI: 10.1123/ijspp.8.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Cooling and Performance Recovery of Trained Athletes: A Meta-Analytical Review

Abstract: Purpose:Cooling after exercise has been investigated as a method to improve recovery during intensive training or competition periods. As many studies have included untrained subjects, the transfer of those results to trained athletes is questionable.Methods:Therefore, the authors conducted a literature search and located 21 peer-reviewed randomized controlled trials addressing the effects of cooling on performance recovery in trained athletes.Results:For all studies, the effect of cooling on performance was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 51 publications
3
98
1
3
Order By: Relevance
“…Roberts and colleagues 16 reported that CWI following a conventional resistance training session (consisting of back squats, front squats, walking lunges and drop jumps) did not improve recovery of maximal strength and power at two or four hours post recovery compared to an active recovery. Jakeman and colleagues 15 reported that following ten sets of ten countermovement jumps, CWI provided no additional benefit compared to the control group 6 Poppendieck and colleagues 6 reported that there were negligible differences (-1%) in performance following short-term (two-three hours) recovery periods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Roberts and colleagues 16 reported that CWI following a conventional resistance training session (consisting of back squats, front squats, walking lunges and drop jumps) did not improve recovery of maximal strength and power at two or four hours post recovery compared to an active recovery. Jakeman and colleagues 15 reported that following ten sets of ten countermovement jumps, CWI provided no additional benefit compared to the control group 6 Poppendieck and colleagues 6 reported that there were negligible differences (-1%) in performance following short-term (two-three hours) recovery periods.…”
Section: Discussionmentioning
confidence: 99%
“…17 whereas the upper-body eccentric based training investigations only immersed the working arm. In the meta-analysis by Poppendieck and colleagues 6 it was reported that full-body CWI was more effective in improving performance than partial immersion. Based on the existing literature, water immersion only appears to be more effective than passive recovery (for improving maximal strength and power) when it involves whole body immersion, and is used after severe lower-body muscle-damaging exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51,72,73 A recent meta-analytical review 24 found that precooling improved exercise performance by a factor of 5.7% overall, with mixed cooling methods (ie, CWI and cooling vests) providing the largest improvement in exercise performance (7.3%) Cooling postexercise has also been investigated in that cooling the body postexercise allows athletes to recover more quickly and thus have the potential to improve their performance in subsequent competition. 11,13 It is postulated that high internal thermal loads, often seen after intense exercise in the heat, result in the degradation of exercise performance and lengthen the time for the body to recover. 2 Furthermore, it is believed that exercise-induced hyperthermia causes a centrally mediated reduction in voluntary muscle activation and force that can have adverse effects on performance.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the level of stress on the body after exercise by lowering body temperature helps the body recover more quickly and thus allows it to perform better in subsequent training sessions or competitions. 11 Postexercise cooling has been shown to reduce inflammation, heart rate, and cardiac output and to provide analgesic effects that can assist in reducing recovery time. [12][13][14] At rest, body temperature is closely regulated at or close to 37°C.…”
mentioning
confidence: 99%